(untitled) (Global Journal of Science Frontier Research, 2014)
An aquatic biodiversity analysis was conducted in four rice terraces clusters in the Cordillera region in the northern central part of the Philippines. Data was obtained using the quadrat sampling method. The location of sampling activities are the four rice terraces clusters namely: (1) Asipulo, Ifugao; (2) Natonin, Mt Province; (3) Bagumbayan, Kalinga; and (4) Tanglagan, Apayao. Each place of sampling had two (2) blocks: (1) Rice paddy fields and (2) Irrigation canals/creeks. The number of quadrats randomly taken in each block was ten (10) plots with each quadrat measuring 1m x 1m. The number of plots in all places was 4 sites x 2 blocks x 10 plots = 80 plots. Individuals of shell, crab, fish and frog species circumscribed within plot/quadrat boundaries were counted, identified and sorted according to species. The importance value (IV) of each species in each block was determined. This was done by taking the sum of Relative Density (%) and Relative Frequency (%) of each species in a given block. Importance Value = Relative Density + Relative Frequency. The Shannon Wiener Diversity Index (H), Evenness Index (E) and Simpson’s Index (C) was obtained for each species. The higher values of H, E and C means the greater diversity character of the community being evaluated.